Recent Development of Bone-Conductive Microphone in DSP - Amaresh Kumar, Dr. Manish Mishra, Roopak Kumar Verma, (International Journal of Scientific Research and Management (IJSRM), 2014)
This article presents recent developments on ongoing challenges in bone conduction hearing devices. Inview of the large number of problems and challenges in electronics for medical devices, this articlefocuses on areas that will advance bone conductive microphone devices for hearing aids. It will bedescribed in greater details in the upcoming that the bone conduction microphone need to receiveincreasing attention and have found uses in many aspects of voice signal processing . This device canimprove the quality of life for patients suffering from different hearing aids and make it feasible to usethis technology all over the world.